3D virtual reality experiments to promote electrical engineering education - Manuel T. Valdez (2015)
3D Virtual Labs are the support of learning, a tool of education in the future. Learning in a 3D environment allows greater interaction with contents in a unique way as students perceive it as being really there. Simulations are being designed, a combination of real-world environment with the information supplied by devices, where measurements can be replicated and data analyzed. This study presents a virtual scenario of a Measurements and Instrumentation laboratory. Electrical Engineering courses aim to train students to succeed in meeting the challenges within competitive and everchanging professional contexts. In order to prepare undergraduate students for ongoing success, the courses must provide effective training in the application and development of practices, typically implemented in large projects and organizations. Developing high quality engineering course units is definitely a challenging task. Courses can be provided remotely, but careful planning is required to design quality course units because problems may occur in meeting quality targets. The developments in information and communication technologies (ICT), including multimedia and internet-based education platforms, facilitate the creation of reliable solutions to these challenges. Studies show that a smart application of multimedia technologies and webbased education platforms can provide great results towards better quality of engineering courses. Many challenges on how to suitably approach the educational process have already been put forward. Higher Education institutions use multiple approaches to teaching and learning, combining a range of methods, including e-learning, videoconferencing, face-to-face teaching and hard-copy resources in course delivery. The authors present a software model for engineering, which is based mainly on the Wirefusion® software, and a virtualreality platform called VEMA. The project intends to improve the quality of teaching and learning in higher education through effective application of information technologies and the sciences of learning. 3D virtual learning environments arise as solutions to the extent that, in addition to offering features associated with communication and information sharing, they promote flexible learning spaces and moments. At the level of higher education, and in accordance with the paradigm of Bologna, virtual environments acquire special importance to allow learning beyond the classroom time and space.